Kenali Risiko, Bukan Tanpa Alasan: Edukasi Bahaya Pacaran Dan Seks Bebas Bagi Remaja Sma 1 Desa Kudu Ganting - Rakimahwati Rakimahwati; Aliya Sasikirana Putri Irsa; Nicholas Tammara; Dhia Awra; Zakia Salsabila; Ifla Anifa (CV. ITTC INDONESIA, 2026)
This community service program aims to increase awareness and understanding among students of SMA 1 Desa Kudu Gantingregarding the dangers of early dating and free sex through comprehensive education. The activity was implemented using a descriptive qualitative approach that adopted a participatory action model, with students in grades X, XI, and XII as the main participants. Prior to implementation, the team prepared presentation materials and conducted internal discussions. On the day of the activity, participants were introduced to reproductive health concepts, the dangers of early dating, and the risks of free sex through an interactive presentation, group discussions, case simulations, and open Q&A sessions. Participants also learned to recognize signs of risky behavior and strategies for refusing peer pressure. Results showed high enthusiasm and active participation among participants. This activity successfully encouraged students to realize that every choice has consequences, and that delaying intimate relationships until the right time is a form of self-love and care for the future.